An acellular tissue engineered biomimetic wound healing device created using collagen and tropoelastin accelerates wound healing. Issue 3 (August 2022) - Diller, Robert B.; Kellar, Robert S.
Abstract: Aim: Tissue engineering has historically involved research combining scaffolds, cells, and active biomolecules to treat multiple pathologies. The current research seeks to determine if the wound healing cascade can be modulated using acellular scaffolds, engineered to create an acellular electrospun dermal biomimetic. Methods: The dermal biomimetic has a similar architecture to the dermis, porosity and fiber diameter, as well as physiologically relevant ratios of the primary structural dermal proteins, collagen and tropoelastin. This biomimetic wound healing device (BMWHD) was implanted into a full thickness dermal wound murine model for six days. Results: WHD-treated wounds had 30% greater re-epithelialization with a thicker epidermis, new elastin fibers in the wound bed, and healed architecture that matched unwounded extracellular matrix. Conclusions: Using these WHDs that closely match the native architecture and protein concentrations, accelerated the wound through the wound healing cascade and supports the hypothesis that structure alone can influence function when engineering acellular dermal biomimetic devices. Highlights: Wound healing evaluation of an electrosun device consisting of tropoelastin. Protein composition and device structure ensure wound healing success. Acellular device able to heal wounds with similar results as cellularized devices. SEM imaging verifies the dermal structure is returned to normal following healing.